2022
DOI: 10.29303/jppipa.v8i1.1067
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Digital Literacy and Learning Outcomes in Biology Learning for Students

Abstract: The study aims to determine the relationship between digital literacy and the learning results on the biology of class vii for the 12th country school class vii. This type of research is a quantitative study with a correlational method. The population in this study is class vii in the 12 countries' middle schools. The samples used in this study number 88 students. Research instruments using tankettes. The data analysis technique used is by using a product-moment correlation. Studies show the class vii c, d, e,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Through years of training, campus journalists could acquire skills that are essential in writing their social media posts to inform others or when writing their essays. Self-efficacy refers to an individual's belief in their own capability to successfully execute a particular behavior or task to produce a desired outcome [45][46][47] . Some students feel confident in writing their essays and articles because they have background in campus journalism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Through years of training, campus journalists could acquire skills that are essential in writing their social media posts to inform others or when writing their essays. Self-efficacy refers to an individual's belief in their own capability to successfully execute a particular behavior or task to produce a desired outcome [45][46][47] . Some students feel confident in writing their essays and articles because they have background in campus journalism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Learning through digital sources in the 21 st century can occur effectively if students can practice digital literacy combined with self-regulation abilities (Greene, Yu & Dana, 2014). Various studies have shown that there is a positive and linear relationship between self-regulated learning and learning outcomes (Sebesta & Speth, 2017;Hidayat, 2021), digital literacy and learning outcomes (Giovanni & Komariah, 2019;Hafiza, Rahayu & Kahar, 2022), as well as self-regulated learning and digital literacy with overall learning outcomes (Lee, Moon & Cho, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The development of the digital world must be filled with positive cultural growth including digital literacy (Sangaji & Pribadi, 2023). Every individual needs to understand that digital literacy is an important thing needed to be able to participate in today's modern world (Hafiza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%